2019
DOI: 10.36469/9731
|View full text |Cite
|
Sign up to set email alerts
|

A Pragmatic Clinical Trial to Compare the Real-World Effectiveness of V-Go versus Standard Delivery of Insulin in Patients with Advanced Type 2 Diabetes

Abstract: Background: Many patients with type 2 diabetes mellitus (T2DM) do not have adequate glycemic control, leading to poor patient outcomes and high healthcare costs. Objective: This prospective pragmatic clinical trial evaluated V-Go, a wearable insulin delivery device, compared with standard treatment optimization (STO) among insulin-treated patients with T2DM in a realworld, community-based practice setting. Methods: Study sites, rather than individual patients, were randomized to V-Go or STO via cluster rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 23 publications
1
19
0
Order By: Relevance
“…Patient impressions of V-Go were generally high across all questions surveyed in this study, which is consistent with previous treatment satisfaction surveys [9,16]. V-Go ease of use compared to previous therapy received the highest rating (8.7 out of 10), which is significant considering that regimen complexity and patient satisfaction can both impact patient compliance, which is critical to improving glycemic control [19].…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Patient impressions of V-Go were generally high across all questions surveyed in this study, which is consistent with previous treatment satisfaction surveys [9,16]. V-Go ease of use compared to previous therapy received the highest rating (8.7 out of 10), which is significant considering that regimen complexity and patient satisfaction can both impact patient compliance, which is critical to improving glycemic control [19].…”
Section: Discussionsupporting
confidence: 87%
“…Cziraky and colleagues reported findings from a randomized controlled trial comparing V-Go to standard treatment optimization (STO). In this study, both therapies significantly reduced HbA1c from baseline V-Go (− 1.0%, P < 0.001) and STO (− 0.5%, P < 0.001); however, V-Go resulted in a significantly (P = 0.002) larger reduction [16].…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…Previous studies showed that switching patients from traditional insulin delivery modes (insulin pens or syringes) to V-Go was associated with significantly improved glycemic control. 7,[11][12][13][14][15][16][17][18][19] This retrospective study represents the largest RWE study to date evaluating the use of V-Go across multiple practices. The objective of the study was to evaluate clinical outcomes in patients with sub-optimally controlled diabetes transitioned from other traditional modes of insulin delivery to V-Go.…”
Section: Introductionmentioning
confidence: 99%